"Many Seasons Ago": Slavery and Its Rejection among Foragers on the Pacific Coast of North America. Issue 2 (2nd April 2018) - Wengrow, David; Graeber, David
ABSTRACT: Anthropologists have traditionally classified foragers on the Pacific coast of North America into two major culture areas, characterized by strikingly different social and ethical systems. These are "California" and the adjacent "Northwest Coast." Foragers in the northern part of California exhibit many elements of Weber's "Protestant ethic, " such as the moral injunction for community leaders to work hard, seek spiritual purpose by introspection, and pursue monetary wealth while avoiding material excess. By contrast, the social organization of Northwest Coast foragers bears comparison with that of courtly estates in medieval Europe, where a leisured class of nobles achieved status through hereditary ranking, competitive banquets, dazzling aesthetic displays, and the retention of household slaves captured in war. Remarkably, the coexistence of two such clearly opposed value systems among foragers inhabiting adjacent parts of the Pacific littoral has excited little interest in anthropologists, historians, or archaeologists to date. We consider the implications, which cast doubt on some key orthodoxies concerning the nature of culture areas, modes of subsistence, and political evolution. We argue that the political creativity of foraging peoples has been severely underrated. [ hunter‐gatherers, slavery, schizmogenesis, culture areas, North America ]